Sustainable development of a researcher's career trajectory - Johannes Rossouw (Perspectives in Education, 2022)
The ongoing Covid-19 pandemic has taught everyone that longterm planning and execution, which have always been taken for granted, are not a given. In many contexts, stagnation was the initial outcome of hard lockdowns. As international travel ground to a halt, the lack of mobility seriously hampered scholarly personal interaction as an essential part of the career development of especially early-career researchers. While the focus of this paper is not on the current or future effects of the pandemic, the temporary inaction associated with Covid might be seen as a wake-up call for an active, rigorous effort towards sustainable development. Education faculties and their research entities have a duty towards both earlycareer and established researchers to develop strategies through which a steady development path can be maintained despite local, national and international disruptions. The notion of sustainable development of researchers’ career trajectories implies a long-term approach to incessant growth, expansion and skills improvement, leading to maintained and increased productivity as well as higherquality research outputs. This paper explores strategies that may be followed by authorities and individuals that focus on a positive career trajectory for both early-career and established researchers. The question to be answered is how continuous development can be facilitated. The answers lie, inter alia, in stimulating a lifelong interest in research during pre-graduate and doctoral students’ introduction to research theory and practice, constantly building capacity through increased research skills levels. Mentorship offered by established researchers can also be seen as part of their own prolonged development. In addition, of equal importance is the development of the ability among individual researchers and project groups to take responsibility for their own career trajectory.